2022
DOI: 10.1161/jaha.122.026960
|View full text |Cite
|
Sign up to set email alerts
|

Procedural Outcomes After Percutaneous Coronary Interventions in Focal and Diffuse Coronary Artery Disease

Abstract: Background Coronary artery disease (CAD) patterns play an essential role in the decision‐making process about revascularization. The pullback pressure gradient (PPG) quantifies CAD patterns as either focal or diffuse based on fractional flow reserve (FFR) pullbacks. The objective of this study was to evaluate the impact of CAD patterns on acute percutaneous coronary intervention (PCI) results considered surrogates of clinical outcomes. Methods and Results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 29 publications
1
6
0
Order By: Relevance
“…MSA, an independent predictor of stent failure, was significantly smaller in vessels with low PPG (diffuse disease). 15 , 30 Interestingly, this was not driven by vessel size, because reference vessel diameter was similar between vessels with focal or diffuse disease. It can be hypothesized that the association between diffuse hemodynamic disease and small MSA was partly mediated by the underlying plaque.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…MSA, an independent predictor of stent failure, was significantly smaller in vessels with low PPG (diffuse disease). 15 , 30 Interestingly, this was not driven by vessel size, because reference vessel diameter was similar between vessels with focal or diffuse disease. It can be hypothesized that the association between diffuse hemodynamic disease and small MSA was partly mediated by the underlying plaque.…”
Section: Discussionmentioning
confidence: 98%
“…Optimal procedural results were defined as MSA >5.5 mm 2 and post‐PCI FFR >0.90. 15 Cardiac biomarkers and an ECG were collected 6 to 24 hours after the procedure. To allow for comparison among different troponin assays, values were normalized to the assay‐specific 99th percentile upper reference limit.…”
Section: Methodsmentioning
confidence: 99%
“…In this context, compared with wire-based physiology, QFR has a theoretical additional advantage, as it may allow to predict beforehand the functional result of the angioplasty. This could be crucial in the daily catheterization laboratory practice to detect the subgroup of lesions that will not significantly improve after PCI, avoiding overtreatment and the use of unnecessary stents (with all the procedure-related complications and the long-term risk of intra-stent restenosis) [30]. Recently, the AQVA trial demonstrated that QFR-based virtual PCI was superior to conventional angiographybased PCI at achieving an optimal post-PCI physiology result (defined as a post-PCI QFR value ≥ 0.90).…”
Section: Discussionmentioning
confidence: 99%
“…The intervention in vessels with high PPG (focal disease and average PPG 0.80 ± 0.06) resulted in higher post-PCI FFR compared to low PPG (diffuse disease and average 0.58 ± 0.09), (0.91 ± 0.07 focal vs. 0.86 ± 0.05 diffuse group, P < 0.001), and greater stent area (6.3 ± 2.3 mm 2 vs. 5.3 ± 1.8 mm 2 , P = 0.015). The authors stated that PPG significantly improved the capacity to predict optimal PCI results compared with an angiographic assessment of CAD patterns (area under the curve PPG 0.81 [95% CI, 0.73–0.88] vs. area under the curve angio 0.51 [95% CI, 0.42–0.60]; P < 0.001) ( 19 ). Regarding post-PCI angina, in a sub-study of TARGET—FFR (Trial of Angiography vs. pressure-Ratio-Guided Enhancement Techniques—Fractional Flow reserve), it was shown that patients with focal disease had larger increases in FFR after PCI (0.30 ± 0.14 vs. 0.19 ± 0.12; P < 0.001) and less angina assessed by the Seattle angina questionnaire (SAQ-7) [87.1 ± 20.3 vs. 75.6 ± 24.4; mean difference = 11.5 (95% CI: 2.8–20.3); P = 0.01] compared to patients with diffuse disease assessed by PPG.…”
Section: The Methods To Evaluate Serial Stenosesmentioning
confidence: 99%